A modification of the leaf-nets method for sampling benthic invertebrates in spring habitats - Di Sabatino, Antonio; Cristiano, Giovanni; Vignini, Patrizia; Miccoli, Francesco Paolo; Cicolani, Bruno (Journal of limnology, 2018)
The full ecological potential of spring habitats remains relatively unexplored mostly because of the lack of standardized sampling procedures and difficulties to collect representative biological samples, especially in small-sized springs. Recent studies on sampling methodologies in spring habitats indicated that a modified Surber net with a reduced frame area, reliably describes the structure and composition of spring communities. This method, however, is very invasive and may severely impact the spring, especially when a large number of samples is required. The paper presents a new quantitative method (leaf-nets) for sampling crenic invertebrates which combines a rather high efficiency with negligible impacts on spring habitat structure and biota. The effectiveness of the new methodology was tested in a medium-size rheocrene spring in Central Apennine, where spring assemblages were sampled in parallel with a modified Surber net and with the new method. Taxa richness and density were higher in the Surber net, while no between-method differences were recorded for the number of insect taxa and Simpson diversity. Furthermore, the overall functional organization of Surber net and leaf-nets assemblages was very similar. The new method sampled only 25% of the individuals cumulatively collected, but 75% of the total richness, with a good representation of the structure and the functional organization of spring assemblages. In comparison with the Surber net, the negligible loss of information of the new method is highly compensated by its minor invasivity, lower impacts on spring microhabitats and invertebrate populations and by its higher versatility. Leaf-nets could also be used to assess leaf-detritus breakdown in springs, thus allowing a better ecological characterization of these ecosystems.